Account receivable management: debt collection policy of Blueocean Technologies Sdn Bhd / Nur Khalidah Mahashim - Mahashim, Nur Khalidah (Faculty of Business and Management, 2011)
This study provides an analysis on how Blueocean Technologies manage its account receivable. The purpose of this study is to know the debt collection policies used by the company in managing its account receivables. This study is also to identify the effectiveness of the debt collection policy currently used by Blueocean Technologies. As a company that sells product on credit, account receivables are the main role for a good cash inflow so a good management on the account receivable will benefit the company cash flow. In order for the company to survive in the industry, they need to manage their account receivable effectively and collect their receivables efficiently. In this research, I will analyze every detail on the problem occur and would recommend few ways on how to improve the debt collection policy for Blueocean Technologies for better management of account receivables. I attached with the product sales flow chart, account receivable collection flow, and many more for the use of this research. The data and information needed been collected from the articles, journals, newspaper, internet and also from the interview with the Chief Executive Officer and Finance Manager of Blueocean Technologies.